(untitled) (Journal of Innovation in Academia, 2025)
The study aims to identify the most influential factors that affect customer satisfaction and retention in mobile banking and determine their relative impact. The Exploratory research design was adopted as the main research paradigm to discover the reality. The data was evaluated quantitatively by using both descriptive and inferential statistics. Convenience sampling has used data collection and Structural Equation Modeling (SEM) was used to analyze the relationships from 403 responses. The research findings indicated that security, responsiveness, and convenience have a significant impact on customer satisfaction, while cost and relative advantage have a negligible impact. However, although customer satisfaction and loyalty are strongly related, these factors are not directly related to loyalty. This finding holds theoretical relevance for the Service Quality Theory.